2012
DOI: 10.1371/journal.pone.0040225
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Position and Replication Kinetics of Heliothis virescens Ascovirus 3h (HvAV-3h) Isolated from Spodoptera exigua

Abstract: Insect-specific ascoviruses with a circular genome are distributed in the USA, France, Australia and Indonesia. Here, we report the first ascovirus isolation from Spodoptera exigua in Hunan, China. DNA-DNA hybridization to published ascoviruses demonstrated that the new China ascovirus isolate is a variant of Heliothis virescens ascovirus 3a (HvAV-3a), thus named HvAV-3h. We investigated the phylogenetic position, cell infection, vesicle production and viral DNA re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
53
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(54 citation statements)
references
References 41 publications
1
53
0
Order By: Relevance
“…The peptidase also has Y-glutamyl hydrolase activity in humans (1), and GvpU is required to produce gas vesicles in B. megaterium (13). These two genes were not found in the other reported ascoviruses, including the closely related HvAV-3e (12). Five unique homologous regions (hrs) and 25 baculovirus repeated ORFs (bro), which are highly variable, were found in the genome of HvAV-3g.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…The peptidase also has Y-glutamyl hydrolase activity in humans (1), and GvpU is required to produce gas vesicles in B. megaterium (13). These two genes were not found in the other reported ascoviruses, including the closely related HvAV-3e (12). Five unique homologous regions (hrs) and 25 baculovirus repeated ORFs (bro), which are highly variable, were found in the genome of HvAV-3g.…”
mentioning
confidence: 84%
“…A total of 300,000 PE reads were used to assemble a single contig by Edena (11). The assembled contig representing the entire HvAV-3g genome sequence was confirmed by comparing six predicted restriction fragment profiles from the genome, for HindIII, EcoRI, BamHI, XbaI, XhoI, and PstI, with the matching fragment profiles produced by actual restriction digestions of the HvAV-3g genome (7,8,12).…”
mentioning
confidence: 99%
“…A total of 6,244,397 clean pair-end (PE) reads were obtained. Genome assembly was performed using the Edena assembly software package (Hernandez et al, 2008 assembled contig representing the entire HvAV-3f genome sequence was confirmed by six restriction enzyme digestion profiles (BamHI, EcoRI, HindIII, PstI, XbaI and XhoI) that produced the predicted fragments (Cheng et al, 2005;Xue and Cheng, 2011;Huang et al, 2012a). ORFs with 50 aa and longer considered were identified through the GeneMarkS program (Besemer and Borodovsky, 2005), ORF finder (NCBI) and Geneious program (Drummond et al, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…Based on virion morphology, DNA sequence information, host range and tissue tropism, five ascovirus species have been recognized by the International Committee on Taxonomy of Viruses, which are consisting of Spodoptera frugiperda ascovirus 1a (SfAV-1a), Trichoplusia ni ascovirus 2a (TnAV-2a), Heliothis virescens ascovirus 3a (HvAV-3a), and Diadromus pulchellus ascovirus 4a (DpAV-4a) and Trichoplusia ni ascovirus 6a (ex-TnAV-2c) (Bigot et al, 2011). Eighteen isolates or strains belonging to four ascovirus species have been reported in the world (Bigot et al, 2011;Huang et al, 2012a), in which five ascovirus isolates genomes that are SfAV-1a, TnAV-6a (Trichoplusia ni ascovirus 6a, previously named at its discovery TnAV-2c (Wang et al, 2006)), HvAV-3e, HvAV-3g, and DpAV-4a have been sequenced (Wang et al, 2006;Bideshi et al, 2006;Asgari et al, 2007;Bigot et al, 2009;Huang et al, 2012b). All these reported genomes have a double-stranded circular DNA ranging from 100 to 199 kbp in size (Xue and Cheng, 2011;Huang et al, 2012b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation